In vitro biocontrol of Fusarium oxysporum with antagonistic microorganisms and In vivo effect on Solanum lycopersicum L. Issue 8 (3rd August 2022) - Rubio-Tinajero, Sarahi; Osorio-Hernández, Eduardo; Estrada-Drouaillet, Benigno; Silva-Espinosa, José Hugo Tomás; Delgado-Martínez, Rafael; Espinoza-Ahumada, César Alejandro; Ríos-Velasco, Claudio; Torres-Castillo, Jorge Ariel
Abstract: The objective was to evaluate the effects of In vitro biocontrol of Trichoderma spp. and Bacillus spp. against Fusarium oxysporum and its in vivo effect on Solanum lycopersicum plants. The antagonistic effect in vitro of microcapsules of Trichoderma spp. and Bacillus spp. against F. oxysporum, was evaluated by inhibition and antagonism classification, in the in vivo part growth variables in plant and fruit were measured. Trichoderma asperellum showed inhibition of 84.7% and class 1 and Bacillus spp., obtained an inhibition of 83.7% with a positive classification. The canonical correspondence analysis of the fruit, the T1 treatment indicates that the variables that highlight the effect of the treatment are the firmness of the fruit and the Brix. The canonical correspondence analysis of the plant, the height presents a significant difference ( P  < 0.05), highlighting B. subtilis, Bacillus liquefasciens, T. harzianum and T. asperellum + Bacillus amiloliquefasciens, with 1.05 and 1.1 m compared to the control of 74 cm, also highlighted the number of total fruits in the T. harzianum treatment with an average of 22.6 fruits and root weight in B. subtilis with 37.12 g. Strains of Trichoderma spp. and Bacillus spp. successfully inhibited F. oxysporum also induced growth in the tomato plant.